Correction of the Tooth Alignment In Case of the Popov-Godon Phenomenon Using A Dental Implant With Immediate Loading (Clinical Case) - DilanyanK. Mamikon (Journal of Global Pharma Technology, 2018)
This paper describes a clinical example with immediate loading on the dental implant with a temporary (cobalt-chromium alloy crown) that was mounted in the area of the secondary edentulism of tooth 24 with the Popov-Godon phenomenon of its antagonist – tooth 34 – with vertical malalignment and tilt towards the tongue. This pathology is part of the second form and second subgroup thereof. Treatment started with the mounting of a dental implant in the area of the secondary edentulism of tooth 24 with immediate loading on the dental implant, with a view to correcting the impaction of the antagonist tooth 34 into its usual alignment in a continuous dental arch. This work was done in clinical conditions. The patient was examined once every fortnight after the fixation of the temporary pontic. Spot X-ray of the dental implant and tooth 34 was conducted. The work lasted four months. Over the course of the work, all structures were produced once.Keywords: Tooth Alignment, Popov-Godon Phenomenon, Dento-Alveolar Malalignment, Dental Implant, Dental Arches.